Implementasi Kurikulum Merdeka pada Pelajaran Pendidikan Agama Islam di SMPN 13 Malang - Umam, Rizal Khoirul (Universitas Indraprasta PGRI Jakarta, 2024)
Education has a central role in the formation of human character, making it a key element in the development of individuals and society. Education is closely related to the curriculum, the curriculum must be constantly updated to be in line with the needs of the times. In a modern era full of challenges, the curriculum is expected to produce critical, creative, and innovative individuals. This study aims to describe the implementation of Merdeka Curriculum as well as its supporting and inhibiting factors in Islamic Religious Education (PAI) lessons at SMPN 13 Malang. Using a qualitative approach with a case study type, this research was conducted from November 2023 to January 2024. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the implementation of Merdeka Curriculum at SMPN 13 Malang includes learning planning, learning implementation, learning evaluation and the Pancasila Student Profile Strengthening Project (P5). While the supporting factors for implementation include an open mindset, adequate infrastructure, and contextual learning. While the obstacles include a limited budget and facilitators who teach not according to their fields.